Effects of Cooling Rates on Microstructure, Wettability and Strength of Sn3.8Ag0.7Cu Solder Alloy - Siti Rabiatull Aisha, Idris; Nadhrah, Murad; M., Ishak (Elsevier Ltd, 2017)
The aim of this research paper is to study the effects of cooling rates on microstructure and mechanical properties of Sn3.8Ag0.7Cu solder alloy prepared through powder metallurgy (PM) method. They were cooled by different cooling medium such as slow (furnace cooling), normal (air cooling) and fast (water cooling) which was 0.0076°C/s, 0.73°C/s and 31.14°C/s, respectively. Characterisation for each sample was conducted to examine the intermetallic compound formation and solder shear strength. Result indicated that faster cooling rates decreased the IMC thickness but reduced the solder joint strength due to distribution of melted solder on Cu board. This study found that the shape of Cu6Sn5 and Ag3Sn changed according to cooling rates either at the interfacial or in the solder matrix. The study on comparison between three different cooling rates onto properties of Sn3.8Ag0.7Cu solder alloy prepared by PM method is still unknown and the current findings are still unclear. Thus this research would be the fundamental study to investigate the effects of cooling rates onto behaviours of the solder alloy. It is believed that more attentions will be shown onto this superior topic to increase the level of promising reliability of solder alloy in industry and marketplaces.